ПРО ДЖЕРЕЛО РОЗВИТКУ РАКУ ЛЕГЕНІ - Bolgova, L.S.; Tuganova, T.N.; Alekseenko, O.I.; Ponomarenko, A.A. (PH Akademperiodyka, 2023)
In the review on the issues of histogenesis of lung cancer (LC), the significant results of experimental, pathological, immunohistochemical and molecular-biological studies are presented. However, until now, no data has been obtained that would allow scientists to come to an unambiguous decision about the origin and development of this disease. The question remains not yet fully understood, since researchers discuss the origin of LC development in a hypothetical form. This situation poses the task of further in-depth scientific research, which would make it possible to clarify the unambiguous origin of LC development, and, therefore, would allow solving the problem of its early diagnosis and create grounds for screening programs, which is of high scientific and clinical significance.